Validation of the G.LAB MD2200 wrist blood pressure monitor according to the European Society of Hypertension, the British Hypertension Society, and the International Organization for Standardization Protocols. Issue 2 (April 2017) - Liu, Ze-Yu; Zhang, Qing-Han; Ye, Xiao-Lei; Liu, Da-Peng; Cheng, Kang; Zhang, Chun-Hai; Wan, Yi
Abstract : Objective: To validate the G.LAB MD2200 automated wrist blood pressure (BP) monitors according to the European Society of Hypertension International Protocol (ESH-IP) revision 2010, the British Hypertension Society (BHS), and the International Organization for Standardization (ISO) 81060-2:2013 protocols. Materials and methods: The device was assessed on 33 participants according to the ESH requirements and was then tested on 85 participants according to the BHS and ISO 81060-2:2013 criteria. The validation procedures and data analysis followed the protocols precisely. Results: The G.LAB MD2200 devices passed all parts of ESH-IP revision 2010 for both systolic and diastolic BP, with a device–observer difference of 2.15±5.51 and 1.51±5.16 mmHg, respectively. The device achieved A/A grading for the BHS protocol and it also fulfilled the criteria of ISO 81060-2:2013, with mean differences of systolic and diastolic BP between the device and the observer of 2.19±5.21 and 2.11±4.70 mmHg, respectively. Conclusion: The G.LAB MD2200 automated wrist BP monitor passed the ESH-IP revision 2010 and the ISO 81060-2:2013 protocol, and achieved the A/A grade of the BHS protocol, which can be recommended for self-measurement in the general population.